2019
DOI: 10.1111/jofi.12777
|View full text |Cite
|
Sign up to set email alerts
|

Limited Investment Capital and Credit Spreads

Abstract: Using proprietary credit default swap (CDS) data, I investigate how capital shocks at protection sellers impact pricing in the CDS market. Seller capital shocks-measured as CDS portfolio margin payments-account for 12% of the time-series variation in weekly spread changes, a significant amount given that standard credit factors account for 18% during my sample. In addition, seller shocks possess information for spreads that is independent of institution-wide measures of constraints. These findings imply a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…For example,Siriwardane (2019) shows that shocks to the capital of financial intermediaries play a significant role in determining CDS spread dynamics.…”
mentioning
confidence: 99%
“…For example,Siriwardane (2019) shows that shocks to the capital of financial intermediaries play a significant role in determining CDS spread dynamics.…”
mentioning
confidence: 99%
“…A policy maker can remedy this inefficiency by reducing the bargaining power of the seller relative to that of the buyer, for example, by reducing concentration in the provision of credit insurance. This is especially important for the CDS market, in which the sell side is twice as much concentrated as the buy side; see Siriwardane (2018). 3 Our findings suggest that merging safe banks with low initial exposure is not welfare-enhancing.…”
Section: Introductionmentioning
confidence: 81%
“…These papers analyze only the trades that occur for intermediation purposes and thus are silent about the net trading volume. However, Siriwardane () looked at both net and gross volume in the CDS market and he found that not only do intermediaries have higher gross volume than customers, but they also account for higher net selling and net buying volume. To sum up, Proposition is suggestive of the fact that these empirical findings corroborate the endogenous customer‐intermediary trading patterns that arise from heterogeneity in meeting rates rather than those that arise from heterogeneity in asset positions or exogenous valuations.…”
Section: Equilibriummentioning
confidence: 99%